ON THE ORE AND OIL-BEARING CAPACITY OF NEW MINERAGENIC BELT OF EURASIA - PANOV, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new latent ore-, oil and gas-bearing mineragenetic belt of Eurasia had described. It is by a planet scale and consolidates such geological structures as Brest trough, the Pripyat graben, the Dnieper-Donetsk depression, Donbas, the latent Karpinsky ridge, Mangishlack trough, Sultanuizdag, Bucharo-Khive dislocation zone, S.Tien-Shan at the CIS territory. The perspective prognosis ore-, oil-, and gas-bearing estimate of the indicated structures had done and it be worthy of further exploring by common efforts of specialists of different countries.